2017
DOI: 10.18203/2394-6040.ijcmph20173317
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of hypertension and its socio-demographic factors among adult population in a rural community of Singur block, Hooghly district, West Bengal

Abstract: Background: Non-communicable diseases (NCD) are the leading cause of adult mortality and morbidity worldwide now days. The NCD like hypertension is emerging as a major health problem in India with increasing prevalence significantly in both urban and rural population. The objectives of the study were to find out the prevalence of hypertension and its association with socio-demographic factors among the study subjects, if any. Methods: This cross-sectional study was conducted from May, 2013 to April, 2014 in ru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 9 publications
1
0
1
Order By: Relevance
“…Comparatively, the prevalence of hypertension in the current study is lower than the prevalence of hypertension (26.1%) observed in west Bengal rural community in 2017 [16]. Similarly, recent studies conducted in south western Nigeria also reported a slightly higher prevalence of (31.6%) [17], 20.8% [18] and 26.4%, similar higher prevalence of hypertension 28.3% [19] was reported in Ethiopia Open Journal of Applied Sciences and 32% in Ghana [20].…”
Section: Prevalence Of Hypertensioncontrasting
confidence: 47%
“…Comparatively, the prevalence of hypertension in the current study is lower than the prevalence of hypertension (26.1%) observed in west Bengal rural community in 2017 [16]. Similarly, recent studies conducted in south western Nigeria also reported a slightly higher prevalence of (31.6%) [17], 20.8% [18] and 26.4%, similar higher prevalence of hypertension 28.3% [19] was reported in Ethiopia Open Journal of Applied Sciences and 32% in Ghana [20].…”
Section: Prevalence Of Hypertensioncontrasting
confidence: 47%
“…Moreover, consequences discovered significant correlations between patients' awareness of HTN complications and age, gender, and occupation. This outcome is supported by another study [19] who showed a significant correlation between age and patients' awareness of HTN. Furthermore, [20] showed significant associations between the knowledge, and occupation of the respondents respectively.…”
Section: Discussionsupporting
confidence: 68%